Soft-tissue Sarcoma of the Hand: Patient Characteristics, Treatment, and Oncologic Outcomes. Issue 6 (15th March 2021) - Lans, Jonathan; Yue, Kai-Lou C.; Castelein, René M.; Suster, David I.; Nielsen, G. Petur; Chen, Neal C.; Calderon, Santiago A. Lozano
Abstract : Introduction: The aim of this study was to describe patient characteristics, treatment, and oncologic outcomes of soft-tissue sarcomas (STSs) of the hand. Methods: Sixty-nine STSs of the hand in adult patients treated at a tertiary referral center were retrospectively included. We describe patient and tumor characteristics along with oncologic outcomes. Results: Epithelioid sarcoma (23%) was the most common histologic subtype, followed by synovial sarcoma (15%). Of all tumors, 17 (25%) were grade I, 22 (32%) were grade II, and 30 (44%) were grade III. The 5-year disease-free survival for epithelioid sarcomas was 75% with a disease survival of 100%, along with a metastatic rate of 15%. Of the patients with a synovial sarcoma, 40% developed metastases, and the 5-year disease-free survival was 68% and the 5-year disease survival was 73%. Conclusion: Hand STSs are aggressive tumors with a high metastatic potential. Even with adequate oncologic treatment, long-term clinical follow-up (10 years) in these tumors is advised. The treating surgical oncologist should not be deceived by their smaller size.